x(5x – 3) – x^2 (x – 1) + x(x^2 – 6x) – 10 + 3x

Question

x(5x – 3) – x^2 (x – 1) + x(x^2 – 6x) – 10 + 3x

in progress 0
Delilah 1 tháng 2021-08-31T06:11:14+00:00 2 Answers 17 views 0

Answers ( )

    0
    2021-08-31T06:12:18+00:00

    Đáp án:-10

     

    Giải thích các bước giải:

        x(5x – 3) – x^2 (x – 1) + x(x^2 – 6x) – 10 + 3x

    =5x²-3x-x³+x²+x³-6x²-10+3x

    =-10

    0
    2021-08-31T06:12:34+00:00

    Đáp án:

     

    Giải thích các bước giải:

    x(5x – 3) -x²( x -1)+ x(x² -6x)-10+3x

    = 5x² – 3x – x³ + x² + x³ – 6x²-10+ 3x

    = ( 5x² + x² – 6x²)-( x³ – x³) -( 3x – 3x) – 10

    = -10

    Học tốt !

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )